2003
DOI: 10.1029/2002gc000363
|View full text |Cite
|
Sign up to set email alerts
|

Sources of nitrogen and methane in Central American geothermal settings: Noble gas and 129I evidence for crustal and magmatic volatile components

Abstract: [1] Gases and fluids from four geothermal fields of Central America were analyzed for nitrogen, methane, and helium concentrations, isotopic composition, and 129 I/I ratios in order to determine the sources of volatiles in these systems. Results for gas ratios and isotopic compositions for three of the fields are consistent with observations from other subduction zones. Ratios of N 2 / 3 He are only slightly higher than average arc values of 1 Â 10 8 and the volcanic flux of N 2 for the Central American system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 86 publications
(176 reference statements)
14
85
2
1
Order By: Relevance
“…do not allow to clearly discriminate between crustal and magmatic sources. Such a positive isotopic signature is indeed typical of 1) N 2 produced by thermal decomposition of organic material buried in sedimentary material (Jenden et al, 1988;Fischer et al, 2002;Snyder et al, 2003;Inguaggiato et al, 2004) likely involved in the subduction process, and/or 2) low-grade metamorphism affecting NH 4 fixed in the crystal lattices of K-rich minerals (micas and K-feldspars) of crystalline rocks (e.g., Honma and Itihara, 1981;Mingram and Brauer, 2001).…”
Section: Crustal Vs Magmatic Sources In 2010-2015mentioning
confidence: 99%
“…do not allow to clearly discriminate between crustal and magmatic sources. Such a positive isotopic signature is indeed typical of 1) N 2 produced by thermal decomposition of organic material buried in sedimentary material (Jenden et al, 1988;Fischer et al, 2002;Snyder et al, 2003;Inguaggiato et al, 2004) likely involved in the subduction process, and/or 2) low-grade metamorphism affecting NH 4 fixed in the crystal lattices of K-rich minerals (micas and K-feldspars) of crystalline rocks (e.g., Honma and Itihara, 1981;Mingram and Brauer, 2001).…”
Section: Crustal Vs Magmatic Sources In 2010-2015mentioning
confidence: 99%
“…high N 2 /He) in Guatemalan volcanic and geothermal gases show a strong hemipelagic sedimentary signature, whereas Costa Rican gases have low N 2 /He and isotopically light nitrogen, thus supporting a predominant mantle wedge input for the nitrogen Zimmer et al, 2004). Snyder et al (2003) report N 2 /Ar ratios of geothermal wells and fumaroles ranging from $100 to >800 (air = 84) for Nicaragua, and significantly lower ratios ($40 to $100) for Costa Rica. Based on correlations between N 2 /Ar and CH 4 / 3 He ratios as well as 129 I ages, these authors argue that the elevated N 2 /Ar ratios in Nicaragua gases can be attributed to a significant crustal contribution.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The efficiency of nitrogen release from crustal sediments is a temperature-dependent process (Mariner et al, 2003;Snyder et al, 2003). Snyder et al (2003) suggested that the high nitrogen content of Momotombo well gases reflects contribution from a sedimentary basin characterized by nitrogen with positive d 15 N values, mantle 3 He/ 4 He ratios, and high heat flow.…”
Section: Crustal Contaminationmentioning
confidence: 99%
See 2 more Smart Citations